Implementasi Teknik Pelita Sibuntar dan Model PBL untuk Meningkatkan Hasil Belajar Matematika Materi Kesebangunan - Win Eka Rahadyani (Balai Diklat Keagamaan Semarang, 2022)
The purpose of this reasearch is to find out how to implement pelita Sibuntar technic and the PBL Model to improve learning outcomes of similarity materials. The activity is carried out in semester 2 of the 2021/2022 academic year from January to February 2022 with the following stages: Planning, Implementation, and Evaluation. This innovation in learning activities has been proven to significantly improve learning outcomes, the average student learning outcomes are 78.48, with 1 student scoring 100 and the lowest score being 65 and classical completeness 81%. The conclusions from the process of implementing this learning activity are: Teknik pelita Sibuntar and the PBL model can improve the learning outcomes of similarity materials in Mathematics. The implementation of Teknik pelita Sibuntar and the PBL Model can be carried out with the help of LKPD with direct practice using the surrounding environment as a learning resource. t is recommended that teachers manage practice time and use interesting worksheets.